DESCRIPTION OF ORGANIC SEDIMENTS IN THE URINE OF DIABETES MELLITUS PATIENTS AT THE KARO HEALTH CENTER 2019 INTERMEDIATE MATERIALS - Samosir, Alexander; Martin, Stephen; Aulia Nanda, Ficha; Sihombing, Chintani; Karo Karo, Romaida (Universitas Efarina, 2021)
Diabetes Mellitus (DM) is a metabolic disorder with a multifactorial etiology. This disease is characterized by chronic hyperglycemia and affects the metabolism of carbohydrates, proteins, and fats. Examination of the urine sediment is often referred to as microscopic examination. The purpose of this study was to obtain an overview of erythrocytes, leukocytes, bacteria in organic urine sediment in the urine of people with diabetes mellitus. This research is descriptive in nature which was conducted in July 2019 at the Karo Pematangsiantar Health Center. The research sample is 30 samples taken by total sampling method. Data obtained from primary data and secondary data. The results showed that the organic sediment of urine in patients with diabetes mellitus contained abnormal amounts of erythrocytes, leukocytes and bacteria. There were 21 samples of abnormal Erythrocytes (70%) and normal as many as 9 respondents (30%), in 21 samples the number of Leukocytes was above normal i.e. abnormal (70%), in 21 samples the number of Bacteria was abnormal (70%). The results of the study found that there were 9 samples of Normal Erythrocyte counts and 9 abnormal samples, in 9 samples the number of Normal Leukocytes and 9 abnormal samples, in 9 samples the number of Normal Bacteria and 21 samples the number of Bacteria was abnormal in people with diabetes mellitus at the Karo Pematangsiantar Health Center . From the research results are expected to be a scientific contribution and information in enriching knowledge. The results of the study found that there were 9 samples of Normal Erythrocyte counts and 9 abnormal samples, in 9 samples the number of Normal Leukocytes and 9 abnormal samples, in 9 samples the number of Normal Bacteria and 21 samples the number of Bacteria was abnormal in people with diabetes mellitus at the Karo Pematangsiantar Health Center . From the research results are expected to be a scientific contribution and information in enriching knowledge. The results of the study found that there were 9 samples of Normal Erythrocyte counts and 9 abnormal samples, in 9 samples the number of Normal Leukocytes and 9 abnormal samples, in 9 samples the number of Normal Bacteria and 21 samples the number of Bacteria was abnormal in people with diabetes mellitus at the Karo Pematangsiantar Health Center . From the research results are expected to be a scientific contribution and information in enriching knowledge.